CONTENT OF THE REFORMS AIMED AT THE DEVELOPMENT OF THE SPHERE OF THE HIGHER PEDAGOGICAL EDUCATION OF UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
This article discusses the content of the ongoing reforms in the development of higher pedagogical education in Uzbekistan. Opinions were also expressed on the use of foreign educational experience in the reform of the higher pedagogical education system. Special attention is paid to international cooperation in this area.